The angel's prayers: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
"The Angel's Prayers" is a touching narrative that explores themes of faith, hope, and divine intervention. The story typically centers around an angel who hears the prayers of people in need and embarks on a journey to help them. Through various challenges, the angel learns about the power of compassion and the impact of love, ultimately highlighting the importance of believing in something greater than oneself. The tale emphasizes that while prayers may not always be answered in the way one expects, the presence of hope and kindness can lead to profound transformations.